Herbivoria por Atta sexdens rubropilosa Forel, 1908 sobre espécies arbóreas em restauração florestal - Ferreira, Beatriz Zidioti [UNESP] (2015)
Leaf-cutting ants are herbivores that have great potential to shape communities and ecosystems functioning and are therefore considered ecosystem engineers. Most damage caused by leaf-cutting ants occurs in young leaves, thus influencing seedlings establishment and development, possibly delaying the restoration processes. The aim of this study was to verify if leaf-cutting ants can act as a biotic filter determining species composition of communities undergoing restoration, and if they can lead to extinction some species or compromise the structure of restored forests. The study was conducted in a riparian forest undergoing restoration since 1990, at the municipality of Tarumã-SP. We simulated the arrival of forest species to the site being restored, by introducing 20 seedlings of tree species of the regional flora, representing different functional guilds. We planted 20 individuals of each species in a large gap, with about 500 m², surrounded by the existing forest. Planting density was defined based on the density in which plants the same size of the seedlings planted occur in the native forest in the study region. The development of each individual and herbivory by ants were recorded from December 2012 to December 2013. We compared the frequency of herbivory among species and investigated possible patterns of resistance to herbivory associated with functional attributes of the tree species. We also evaluated the effect of selective herbivory on the diversity of the community in restoration through time. From the management perspective, we investigated whether or not the frequency of herbivory by ants is associated with time after planting (acclimation), and if mortality rates depend on the size of the seedlings planted. The frequency of herbivory was different among the tree species planted, resulting in different rhythms and different mortality rates among species. As a consequence, ...